THE EFFECT OF PSYCHOLOGICAL CAPITAL ON ORGANIZATION CITIZENSHIP BEHAVIOR - Fanny Rezkiya; Ade Irma Anggraeni (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
The purpose of this research was to find out the effect of psychological capital on organizational citizenship behavior in the case of nursing employees in RSUD Prof. Dr. Margono Soekarjo. It needs to be explored more deeply about the effect of psychological capital on organizational citizenship behavior to get more complete understanding. The population in this study were civil servant nursing employees who work in RSUD Prof. Dr. Margono Soekarjo. While the sample used in this study were 180 civil servant nursing employees who work in RSUD Prof. Dr. Margono Soekarjo with sampling method of probability sampling and Slovin formula. Data collection method used was survey method with questionnaire. Based on the data analysis using SPSS, it can be concluded that hope, optimism and resilience have positive and significant effect on organizational citizenship behavior.